Estimating historic and recent non-sexual HIV transmission to women in sub-Saharan Africa - David Gisselquist (Frontiers in Public Health, 2026)
Introduction The proportion of HIV infections in sub-Saharan Africa from non-sexual risks has been debated for decades. This article estimates that proportion for women. Methods Use information from studies of discordant couples and from national surveys to estimate women’s incidence from sexual transmission and average male-to-female sexual transmission. Compare those estimates to historic increases in women’s infections and to recent incidence. Results Based on four studies reporting incidence in women in discordant couples and on information from national surveys, annual HIV incidence in women from sexual transmission as a percent of women’s prevalence as well as annual male-to-female transmission averaged across all infected men can both be (generously) estimated at 10%. In 10 of the 11 countries that reached at least 10% adult prevalence, percentages of pregnant women infected in sentinel surveys or estimated numbers of infected women by country increased at compound annual rates of 17–58% for multi-year periods during 1985–2000; if women’s incidence from sexual transmission was 10% of women’s prevalence, non-sexual transmission accounted for an estimated 41–83% of women’s infections during those periods. Similarly, if 10% of men with unsuppressed viral loads sexually infect one woman per year, an estimated 65% of women’s incident infections in 10 national surveys during 2019–25 were from non-sexual transmission. Discussion According to evidence presented here, most HIV infections in women in sub-Saharan have been from blood-borne risks. Investigations of infections suspected from skin-piercing healthcare and cosmetic procedures can find and fix transmitting procedures and warn the public about blood-borne risks.